Effects of P-MAPA immunomodulator on Toll-like receptor 2, ROS, nitric oxide, MAPKp38 and IKK in PBMC and macrophages from dogs with visceral leishmaniasis - Melo, L. M. [UNESP]; Perosso, J. [UNESP]; Almeida, B. F. M. [UNESP]; Silva, K. L. O. [UNESP]; Somenzari, M. A. [UNESP]; Lima, Valéria Marçal Felix de [UNESP] (Elsevier B.V., 2014)
Leishmania (L.) chagasi is the etiologic agent of visceral leishmaniasis (VL) that can be transmitted to humans and dogs. VL in Brazil represents a serious public health problem; therefore, it is important to study new alternatives to treat infected dogs. In dogs, the therapeutic arsenal against canine VL is limited. The immunomodulator protein aggregate magnesium-ammonium phospholinoleate-palmitoleate anhydride (P-MAPA) improves immunocompetence when the immune system is impaired, but its dependence on Toll-like receptors (TLRs) and the mechanisms involved in immune response remain unclear. The in vitro action of P-MAPA on the expression of TLR2 and TLR4, reactive oxygen species (ROS), nitric oxide (NO) and p38 mitogen-activated protein kinase (p38 MAPK) and IKK phosphorylation was studied in mononuclear cells from peripheral blood and macrophages from healthy and Leishmania-infected dogs. The PBMC or macrophages were isolated and cultured with different concentrations of P-MAPA (20,100 and 200 mu g/ml) in a humid environment at 37 degrees C with 5% CO2. Observation revealed that Leishmania-infected dogs showed a decrease in TLR2 in macrophages compared with healthy dogs and in induction with P-MAPA. ROS were increased in PBMCs from Leishmania spp.-infected dogs compared with healthy dogs and P-MAPA improved ROS production. NO production was increased in culture supernatant from macrophages stimulated by P-MAPA in both healthy and Leishmania spp. infected dogs. Treatment of macrophages from healthy dogs with immunomodulatory P-MAPA induced p38 MAPK and IKK phosphorylation, suggesting signal transduction by this pathway. These findings suggest that P-MAPA has potential as a therapeutic drug in the treatment of canine visceral leishmaniasis. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Leishmania sp.; P-MAPA; Dog; Immunomodulatory; TLR